Characterization of electrodes modified with sludge-derived biochar and its performance of electrocatalytic oxidation of azo dyes. (15th December 2022) - Zhang, Chen; Li, Huiqi; Yang, Xue; Tan, Xuejun; Wan, Chunli; Liu, Xiang
Abstract: Pyrolysis of waste sludge in sewage treatment can achieve a substantial reduction in solid waste and obtain sludge-based biochars with multiple functions. However, the electrochemical properties of sludge-derived biochar as electrode modification material and the electrocatalytic ability of biochar-modified electrodes are still unclear. In this study, sludge-based biochars were prepared at various pyrolysis temperatures (400 °C, 500 °C, 600 °C, 700 °C, and 800 °C) and then were cast on glassy carbon electrodes to fabricate composite biochar-electrodes (GC400, GC500, GC600, GC700, and GC800). The results of elemental analysis and Raman spectra showed that sludge-based biochar prepared at higher temperatures exhibited higher aromaticity and degree of defect structures. And the results of cyclic voltammetry and electrochemical impedance spectra confirmed that biochar-modified electrodes prepared at higher temperatures (>600 °C) possessed better electrocatalytic activity and electrochemical stability, and their higher oxygen evolution potential than control test could improve the electrocatalytic efficiency. In the electrocatalytic oxidation of methyl orange, the removal rate with GC800 was the highest, reaching 94.49% within 240 min, and the removal rates with other composite electrodes were 90.61% (GC700) > 86.96% (GC600) > 80.32% (GC). The free radical quenching experiment revealed that the electrocatalytic degradation of methyl orange mainly depended on the indirect oxidation of hydroxyl radicals generated by electrocatalysis, accounting for 81.3% of the removal rate. The biochar-modified electrode not only greatly improved the electrocatalytic ability of the electrode for the degradation of azo dyes, but also achieved the recycling application of products after pyrolysis of sludge waste. Graphical abstract: Image 1 Highlights: Sludge-based biochars were prepared at various pyrolysis temperatures (400–800 °C). Sludge-derived biochars were used as electrode modification materials. Biochar-modified electrode (>600 °C) possessed better electrocatalytic activity. The oxygen evolution potential of biochar-modified electrodes increased up to 1.85 V. The removal rate of methyl orange by electrocatalysis with GC800 reached 94.49%.